Hepatitis E virus replication in human intestinal cells. Issue 5 (14th November 2019) - Marion, Olivier; Lhomme, Sebastien; Nayrac, Manon; Dubois, Martine; Pucelle, Mélanie; Requena, Mary; Migueres, Marion; Abravanel, Florence; Peron, Jean Marie; Carrere, Nicolas; Suc, Bertrand; Delobel, Pierre; et al.
Abstract : Objective: Hepatitis E virus (HEV), one of the most common agent of acute hepatitis worldwide, is mainly transmitted enterically, via contaminated water for HEV genotypes 1 (HEV1) and HEV2, or by eating raw or undercooked infected meat for HEV genotype 3 (HEV3) and HEV4. However, little is known about how the ingested HEV reaches the liver or its ability to replicate in intestinal cells. Design: We developed human primary cultures of small intestine epithelial cells and intestinal explants obtained from small bowel resections. The epithelial cells were also polarised on transwells. Cells were infected with Kernow-p6 strain or clinically derived virions. Results: Primary intestinal cells supported the growth of Kernow-p6 strain and HEV1 and HEV3 clinically derived virions. Polarised enterocytes infected with HEV1 and HEV3 strains released HEV particles vectorially: mostly into the apical compartment with a little basally. Iodixanol density gradient centrifugation of enterocyte-derived HEV virions gave bands at a density of 1.06–1.08 g/cm 3, corresponding to that of quasi-enveloped HEV particles. Ribavirin therapy inhibited HEV excretion from the basal surface but not from the apical side of infected human enterocytes. HEV virions also infected intestinal tissue explants. Lastly, HEV RNA and antigen were detected in the intestinal crypts of a chronically infected patient. Conclusion: HEV can replicate in intestinal cells and reaches the liver as quasi-enveloped virions.